Physiological and behavioral variation by urbanization and climate in an urban-tolerant toad - Monroe, Dillon J.; Bókony, Veronika; Gabor, Caitlin R. (Frontiers in Amphibian and Reptile Science, 2024)
The distribution of a species is best understood by examining the organism-environment interaction. Climate and anthropogenic habitat degradation, including urbanization, are salient features of the environment that can limit species distributions, especially for ectotherms.Comparative studies of the capacity of individuals to cope with rapid environmental change can help us understand the future success or failure of local populations or even the species. Studies of the glucocorticoid stress response are commonly used to understand how species cope with environmental stressors. Glucocorticoids modulate many aspects of physiological homeostasis including changes in energetic allocation and behavior. In a time of global amphibian decline the Gulf Coast Toad (Incilius nebulifer) is increasing its distribution and abundance. To understand how this species deals with thermal and urban stressors, we studied glucocorticoid regulation, hop performance, and lipid storage in I. nebulifer juveniles across nine populations that differed in average annual temperature and level of imperviousness (as an indication of urbanization). We measured corticosterone release rates at baseline, during agitation stress, and during recovery; then measured locomotor performance and whole-body lipids. We tested if I. nebulifer in hotter temperatures and more urbanized habitats exhibits elevated baseline corticosterone levels and either a reduced corticosterone stress response ("stress resistance" hypothesis) or quick poststress recovery by negative feedback ("on again, off again" hypothesis). We also tested whether they exhibit reduced fat stores and decreased locomotor performance as costs of dealing with thermal and urban stressors. We found that I. nebulifer showed elevated baseline and agitation (stressed-induced) corticosterone release rates, and higher lipid storage with increasing urbanization. Climate had quadratic effects on these traits, such that populations living at the lowest and highest temperatures had the lowest corticosterone release rates and lipid stores, and the highest hop performance was observed in the least urbanized site at the warmest climate.Additionally, the rate of glucocorticoid recovery after agitation (negative feedback) decreased with increasing temperature and increased with increasing urbanization. These results indicate that I. nebulifer follows the "on again, off again" hypothesis in an adaptive pattern, which may help them cope with environmental change in terms of urbanization and climatic differences.